Follicular mucinosis - Case report - Paola C. Vieira da Rosa Passos; Manuela Ferrasso Zuchi; Andréa Buosi Fabre; Luis Eduardo A. Machado Martins (Sociedade Brasileira de Dermatologia, 2014)
Follicular mucinosis, also known as alopecia mucinosa, is a cutaneous mucinosis histologically characterized by accumulation of dermal type mucin in the pilosebaceous follicle and sebaceous glands. It presents in two forms, a primary or idiopathic form and a secondary form associated with various benign or malignant processes. Among the malignant processes, the main association is with mycosis fungoides. The frequent overlap of clinical, histopathological, immunohistochemical and molecular biology characteristics makes the correct classification of these conditions difficult, therefore a long follow-up of all cases is recommended. We report the case of an adolescent with disseminated lesions and discuss the difficulty of early identification of secondary follicular mucinosis associated with cutaneous lymphoma.